Indegeneity of knowledge: criteria for universalisation - Farooqui, Jamil (Serial Publications, 2012)
Knowledge, as a matter of fact, should be universal, applicable, at least, to the most situations but it is seldom possible in case of knowledge about human and social world. It is said that knowledge is, to a great extent, conditioned by existential conditions. This is apparent when the relevance and applicability of social sciences to the rest is considered and evaluated by Third World social scientists. They observe that social sciences as developed in the West are indigenous and not applicable to the rest. Thus, they felt the need of indigenisation: to study social realities within their own socio-cultural context. The epistemological issue here is whether knowledge based on indigenous conditions is relevant to other societies and whether universality in knowledge is possible. The paper suggests that it is possible if we develop knowledge taking into consideration three factors: the identification of Absolute Reality and on that basis the construction of other realities, the linkage between truth and goodness and the balance between individual aspirations and societal needs.